EDUKASI MASYARAKAT TENTANG PENTINGNYA MENJAGA KEBERLANJUTAN EKOSISTEM TERIPANG - Indah, Dwi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The high market demand has driven excessive harvesting practices without considering sustainability, resulting in a drastic decline of sea cucumber populations in various coastal areas, with several species now threatened with extinction. This Community Service Program aimed to educate fishers on the importance of maintaining sea cucumber ecosystem sustainability by increasing their understanding of its ecological functions and the long-term economic value of sustainable utilization. The method employed was a participatory approach involving 10 sea cucumber fishers in Soop Island, Sorong City, through socialization and interactive discussions. The results showed an increase in participants’ knowledge and awareness regarding the ecological role of sea cucumbers, threats to their populations, and sustainable management strategies such as the implementation of sasi. Participants also began to commit to environmentally friendly practices, including harvesting only permitted sea cucumber species and supporting local conservation policies such as sasi. Therefore, this educational activity plays a strategic role in aligning economic and ecological benefits while supporting the sustainability of resources and the livelihoods of coastal communities in the future